Possible association of HLA class-I Molecules with autoimmune Hepatitis in Iraqi patients - AL-Obeidy, Eman Sh.; Mousawy, Khalida M.; AL-Akayshi, Raghad J H; Kamil, Laith A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: genetic factors were considered to play a possible role the development of autoimmune hepatitis. Patients and methods: polymerase chain reaction-sequence specific primers (PCRSSP) was the method used to asses HLA-typing of 100 blood samples of 60 AIH patients and 40 healthy normal controls. Results: comparison between AIH patients and healthy controls showed several antigens deviations in their frequencies. HLA-A*113 (A1/-/Null) observed to play a possible risk factor in this disease while significant loss of HLA-A*2 allele were clearly observed which prompt us to believe that it could act as a protective factor, on the other hand, increased frequency of HLA-B*8 & B*14 were statistically significant in AIH which is most likely to be considered as a rather risk factor, while most HLA-B*16 were lost which led us to think of being acting as a rather protective factor. Conclusions: this finding reflects a preliminary picture that HLA antigens might play a role in AIH susceptibility and further studies are worth being carried out.